FAKTOR FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON KEUANGAN DI BEI - Muhammad Arief Effendi; Melke (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study was to determine the effect of the independent variables on the board of director, board of independence, audit quality, managerial ownership, tax aggressiveness, institusional ownership and controlling ownership on the dependent variable of earnings management. Earnings management variable was measured using discretionary accruals using the 2005 Kothari model. This study uses non-financial companies listed on the Indonesia Stock Exchange for the 2017-2020 period. There are 86 companies according to the criteria of the purposive sampling method. This study uses IBM SPSS V25 as an application to manage data. The result showed that audit quality has a negative effect on earnings management. Meanwhile, the board of directors, board of independence, managerial ownership, tax aggressiveness, institusional ownership and controlling ownership have no effect on earnings management.